Identification of differentially expressed genes and signaling pathways in Gaoyou duck ovary at different physiological stages - Zhang, Lei; Xie, Jun; Sun, Guobo; Ji, Rongchao; Li, Xiaoming; Zhang, Xue; Wang, Jian (Frontiers in Veterinary Science, 2023)
Introduction Gaoyou duck is famous in China and abroad for its good production of double-yolk eggs. However, there has been no systematic research on the egg-laying characteristics of the Gaoyou duck, which limits the development and utilization of breed resource. Methods To identify the essential genes related to ovarian development, the transcriptome profiles of the ovaries of Gaoyou ducks at different physiological stages were analyzed. The transcriptome profiles of the ovaries of Gaoyou ducks at 150 d (before laying), 240 d (egg laying) and 500 d (nesting) were constructed, and the differentially expressed genes (DEGs) underwent GO (gene ontology) and KEGG (Kyoto Encyclopedia of Genes and Genomes) analyses. Results The 6 randomly selected DEGs were verified by real-time fluorescent quantitative PCR that their relative expression was consistent with the transcriptional expression profile. Furthermore, KEGG analysis found that 8 candidate signaling pathways were essential for ovarian development, including the MAPK signaling pathway, Progesterone-mediated oocyte maturation, Cell adhesion molecules (CAMs), NOD-like receptor signaling pathway, ECM-receptor interaction, Focal adhesion, TGF-beta signaling path-way and Phagosome. Finally, 5 key DEGs were identified to participate in ovarian development, including TGIF1, TGFBR2, RAF1, PTK2 and FGF10. Discussion Our findings reveal the mechanisms under-lying the molecular regulation of related genes in Gaoyou duck ovarian development.